Diversity and functions of the sheep faecal microbiota: a multi‐omic characterization. Issue 3 (6th February 2017) - Tanca, Alessandro; Fraumene, Cristina; Manghina, Valeria; Palomba, Antonio; Abbondio, Marcello; Deligios, Massimo; Pagnozzi, Daniela; Addis, Maria Filippa; Uzzau, Sergio
Summary: Little is currently known on the microbial populations colonizing the sheep large intestine, despite their expected key role in host metabolism, physiology and immunity. This study reports the first characterization of the sheep faecal microbiota composition and functions, obtained through the application of a multi‐omic strategy. An optimized protocol was first devised for DNA extraction and amplification from sheep stool samples. Then, 16S rDNA sequencing, shotgun metagenomics and shotgun metaproteomics were applied to unravel taxonomy, genetic potential and actively expressed functions and pathways respectively. Under a taxonomic perspective, the sheep faecal microbiota appeared globally comparable to that of other ruminants, with Firmicutes being the main phylum. In functional terms, we detected 2097 gene and 441 protein families, finding that the sheep faecal microbiota was primarily involved in catabolism. We investigated carbohydrate transport and degradation activities and identified phylum‐specific pathways, such as methanogenesis for Euryarchaeota and acetogenesis for Firmicutes. Furthermore, our approach enabled the identification of proteins expressed by the eukaryotic component of the microbiota. Taken together, these findings unveil structure and role of the distal gut microbiota in sheep, and open the way to further studies aimed at elucidating its connections with management and dietary variables in sheep farming. Abstract : This study reports the first characterization of the sheep faecal microbiota composition and functions, obtained through the application of a multi‐omic strategy. 16S rDNA sequencing, shotgun metagenomics and shotgun metaproteomics were applied to unravel taxonomy, genetic potential, and actively expressed functions and pathways, respectively, of the microbial communities inhabiting the sheep distal gut.